Anti-racism and Universal Design for Learning: Building Expressways to Success - Coy, Kimberly; Coy, Kimberly (Educational (Re)naissance, 2023)
Antiracism and Universal Design for Learning: Building Expressways to Success by Andratesha Fritzgerald is a valuable resource for educators, researchers, and policymakers interested in addressing racial disparities in education. The book expertly weaves together theoretical frameworks from Antiracism and Universal Design for Learning to provide a comprehensive understanding of how to create inclusive and equitable learning environments for all students. As a guide for preservice teachers, Fitzgerald breaks new ground on addressing racism and the success of black and brown students.